PERANCANGAN SOAL-SOAL TIPE HIGHER ORDER THINKING SKILLS (HOTS) PADA MATA PELAJARAN INSTALASI TENAGA LISTRIK DI SMKN 6 BANDUNG - Cindy Dwi Lestari, - (2019)
Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat kemampuan peserta didik dalam menalar suatu uji coba instrumen tes Higher Order Thinking Skills (HOTS). Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Pada penelitian ini dapat dijelaskan bahwa instrumen tes yang didapatkan termasuk dalam kategori sangat baik/sangat sesuai dengan aspek yang sudah ditentukan. Berdasarkan data yang diperoleh bahwa peserta didik di SMK Negeri 6 Bandung dalam penalaran soal termasuk dalam kategori cukup, kategori tersebut mengacu kepada Kemendikbud 2014. Sedangkan, tingkat kemampuan berfikir tingkat tinggi peserta didik diketahui bahwa dari 30 peserta didik yang melakukan uji coba lapangan terdapat 10 % peserta didik dengan tingkat berpikir dalam kategori kurang, maka tidak memenuhi 3 deskriptor dalam sistem penskoran HOTS, 33,33 % peserta didik dengan tingkat berpikir cukup pada dimensi pengetahuan konseptual, 50 % peserta didik dengan tingkat berpikir baik pada dimensi pengetahuan prosedural, dan terdapat 6.67 % peserta didik dengan tingkat berpikir sangat baik pada dimensi pengetahuan metakognitif. Abstract. This study aims to determine the level of ability of students in reasoning a test of the Higher Order Thinking Skills (HOTS) test instrument. This research is a descriptive study with a quantitative approach. In this study it can be explained that the test instruments obtained are included in the category of very good / very in accordance with the aspects that have been determined. Based on the data obtained that students at SMK Negeri 6 Bandung in question reasoning are included in sufficient categories, the category refers to the Ministry of Education and Culture in 2014. Meanwhile, the level of high-level thinking ability of students is known that of 30 students who conduct field trials there are 10% students with a level of thinking in the less category, then do not meet the 3 descriptors in the HOTS scoring system, 33.33% of students with sufficient level of thinking on the conceptual dimension of knowledge, 50% of students with a good level of thinking on the procedural knowledge dimension, and 6.67 % of students with very good levels of thinking on the dimensions of metacognitive knowledge.This study aims to determine the level of ability of students in reasoning a test of the Higher Order Thinking Skills (HOTS) test instrument. This research is a descriptive study with a quantitative approach. In this study it can be explained that the test instruments obtained are included in the category of very good / very in accordance with the aspects that have been determined. Based on the data obtained that students at SMK Negeri 6 Bandung in question reasoning are included in sufficient categories, the category refers to the Ministry of Education and Culture in 2014. Meanwhile, the level of high-level thinking ability of students is known that of 30 students who conduct field trials there are 10% students with a level of thinking in the less category, then do not meet the 3 descriptors in the HOTS scoring system, 33.33% of students with sufficient level of thinking on the conceptual dimension of knowledge, 50% of students with a good level of thinking on the procedural knowledge dimension, and 6.67 % of students with very good levels of thinking on the dimensions of metacognitive knowledge.